2010
DOI: 10.1007/s11433-010-4005-2
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt-doping effects in single crystalline and polycrystalline EuFe2−x Co x As2 compounds

Abstract: A series of Co-doped EuFe 2−x Co x As 2 compounds were prepared in both of single crystalline and polycrystalline forms. The Co-doping effects on the crystal structure, electrical resistivity and magnetic susceptibility were systematically studied. Superconductivity was found in polycrystalline Co-doped samples from zero resistivity effects, with the highest onset superconducting transition temperature at 26 K in the optimum doped EuFe 1.84 Co 0.16 As 2 compound. While due to the stronger competition between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(65 citation statements)
references
References 25 publications
1
64
0
Order By: Relevance
“…This similarity suggests that lattice structural effects, rather than the effects of electronic doping, play a fundamental role in tuning the phase diagram in these substitutional studies [35]. However, more detailed investigations are required since other works addressing the substitution of Fe by Co reported that a transition to a superconducting state is realized in a much broader interval of Co substitution [12,36].…”
Section: Resultsmentioning
confidence: 88%
“…This similarity suggests that lattice structural effects, rather than the effects of electronic doping, play a fundamental role in tuning the phase diagram in these substitutional studies [35]. However, more detailed investigations are required since other works addressing the substitution of Fe by Co reported that a transition to a superconducting state is realized in a much broader interval of Co substitution [12,36].…”
Section: Resultsmentioning
confidence: 88%
“…Extensions of the most standard model of inflation (Starobinskiǐ 1979;Guth 1981;Linde 1982) can produce substantial deviations from a Gaussian distribution of primordial density and potential fluctuations (see Bartolo et al 2004;Chen 2010;Desjacques & Seljak 2010 for recent reviews). The amount and shape of this deviation depend critically on the kind of non-standard inflationary model that one has in mind, as will be detailed later on.…”
Section: N O N -G Au S S I a N C O S M O L O G I E Smentioning
confidence: 99%
“…The simplest possible model for the primordial fluctuations consists of a Gaussian random field with a nearly scaleinvariant power spectrum (Bardeen et al 1986). However, many models exist for the inflationary phase (Lyth & Liddle 2009), many of which would alter the statistics of the fluctuations, in particular introducing a non-Gaussian component (Chen 2010). It is therefore important to put observational constraints on the presence (and, once detected, on the amount) of primordial non-Gaussianity (PNG), in order to distinguish between models of the early universe.…”
Section: Introductionmentioning
confidence: 99%